Blockchain Is Changing How Media and Entertainment Companies Compete - Dutra, Andre; Tumasjan, Andranik; Welpe, Isabell (MIT Sloan Management Review, 2018)
Blockchain is poised to help media and entertainment companies build innovative business models that offer new monetization strategies for their digital assets and streamline critical business activities.